Study on Zn-Al-Fe alloys by Ab Initio Molecular Dynamic Simulation - Huan, Zhang; Zhao, Yang Jin; Pu, Hao Zheng; Li, Fu Yi; Xu, Qiang Bao; Yang, Bin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Ab initio molecular dynamics for the Zn-Al-Fe system were measured. The structural and electronic properties of Zn-Al-Fe alloy at different temperatures were simulated. Carried out the Partial Density of State (PDOS), Radial distribution function (RDF), coordination number, Mean square displacement (MSD) and diffusion coefficient of the Zn-Al-Fe system. The simulation results showed that Zn-Al-Fe alloys can be separated easily by vacuum distillation and the best condition was 1073K.